Numerical simulation of axisymmetric drop formation using a coupled level set and volume of fluid method. (September 2016) - Chakraborty, I.; Rubio-Rubio, M.; Sevilla, A.; Gordillo, J.M.
Highlights: The axisymmetric formation of drops is presented numerically. An interface capturing code based on a CLSVOF method is used to perform numerical simulations. The present computations cover the rich dynamics of dripping, jetting and the transition of different responses. The present results are compared successfully with the experimental results of previous investigation. The present predicted results show more accurate than the numerical results obtained from 1D simulations of previous investigation. The existence of new dynamics period-2 with satellite (P2S) response is shown. Abstract: Numerical simulations have been carried out to examine the axisymmetric formation of drops of Newtonian liquid injected from a vertical orifice under constant flow conditions into the ambient air. The numerical simulation was performed by solving axisymmetric Navier–Stokes equations with a coupled level-set and volume-of-fluid (CLSVOF) method. In this work, the dynamics of the formation of drops are investigated over a range of the Ohnesorge number O h = 0.01, 0.023 and 0.13, and the Bond number B o = 0.33, 0.5 and 2.205, as the Weber number We increases. The different responses of drop formation such as period-1 dripping with (P1S) or without satellite drops (P1), complex dripping (CD) and jetting (J) are discussed. The different responses of drop formation were identified quantitatively from the time history of growing length of drop at the orifice. The transition of different responses is shown on the map which exhibits the variation of limiting length of drop at breakup or the volume of the detached primary drop with We while keeping Oh and Bo fixed. The numerical investigation of liquid jet formation in terms of the evolution of growing length of jet under different computational grid sizes was discussed. It is proposed that the almost stable liquid jet formation can be found as the mesh size decreases. The accuracy of the present computed results is assessed by comparisons with the previous investigations. Furthermore, it is shown that at high B o = 2.205, low O h = 0.023 and W e = 0.0177, the system exhibits period-2 with satellite drop (P2S) response which was not reported before in literature.